THE ROLE OF THE UZBEKISTAN SSR IN INTERNATIONAL CULTURAL RELATIONS - Ernazarov Faizullo Narzullaevich (Web of Journals Publishing, 2024)
Cultural cooperation is considered one of the most important components of the system of international relations, and it has served to strengthen mutual respect, trust and solidarity between countries for centuries. In the history of international cultural relations, the land of Uzbekistan has served as a meeting point for various civilizations and the capital of peace, friendship, and culture. From the second half of the 20th century, based on the principle of "Soviet culture", Uzbekistan made a significant contribution to the strengthening of friendship and cooperation between different peoples by widely promoting its culture abroad, especially in the Muslim East. This article reveals the important features of Uzbekistan's cultural relations with Asian countries in the second half of the 20th century.
Keywords: cultural relations, society of friendship and cultural ties with foreign countries,